2007
DOI: 10.1504/ijvas.2007.014945
|View full text |Cite
|
Sign up to set email alerts
|

Model-based predictive control of vehicle dynamics

Abstract: This paper proposes a new model-based hierarchical control strategy for the application of brake torque distribution to vehicle stability control. A three-layer control architecture is adopted, and the focus of the paper is on the intermediate layer which employs a form of model predictive control. To achieve this a non-linear vehicle model is linearised at successive time instants about non-equilibrium operating points. Simulations show that the new controller is more efficient (uses reduced brake authority) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Other authors have suggested alternative, more advanced control methodologies for direct yaw moment control than the integrated PID and FF control structure, such as second order sliding mode control (Canale et al, 2005), internal model control (Canale et al, 2009), linear quadratic regulators (Xiong et al, 2012), model predictive controllers based on conventional and explicit formulations (Chang and Gordon, 2007;Gao et al, 2014), and optimal controllers based on H-infinity and designed using linear matrix inequalities (Fallah et al, 2013;Ahn et al, 2012). There are also limited studies assessing the relative performance of different control structures.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have suggested alternative, more advanced control methodologies for direct yaw moment control than the integrated PID and FF control structure, such as second order sliding mode control (Canale et al, 2005), internal model control (Canale et al, 2009), linear quadratic regulators (Xiong et al, 2012), model predictive controllers based on conventional and explicit formulations (Chang and Gordon, 2007;Gao et al, 2014), and optimal controllers based on H-infinity and designed using linear matrix inequalities (Fallah et al, 2013;Ahn et al, 2012). There are also limited studies assessing the relative performance of different control structures.…”
Section: Introductionmentioning
confidence: 99%
“…For example, regulators based on the Riccati equation [8,15], sliding mode controllers [16] and model predictive controllers [17] are proposed in the literature and already applied in vehicle stability control systems based on friction brake actuation. The wheel torque distribution for the achievement of the reference yaw moment (the control allocation strategy of Figure 2) can be implemented either through rule-based algorithms [18] or the application of optimal control theory [19].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, hierarchical control has not yet been applied extensively to integrated vehicle control system. It is indicated by the relatively small volume of research publications [2,[8][9][10][11][12][13]. In the studies, there are two types of hierarchical control architecture: two-layer architecture [2,[8][9][10] and three-layer architecture [11][12][13].…”
Section: Introductionmentioning
confidence: 99%